Quantum field theory of point particles and strings - Hatfield, Brian; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
First Published in 2018. Routledge is an imprint of Taylor & Francis, an Informa company.
part I POINT PARTICLES -- chapter 1 Introduction: Phenomenology Overview -- chapter 2 First to Second Quantization -- chapter 3 Free Scalar Field Theory -- chapter 4 Free Spinor Field Theory -- chapter 5 Quantization of the Electromagnetic Field -- chapter 6 Interacting Field Theories -- chapter 7 Self-Interacting Scalar Field Theory -- chapter 8 Spinor Quantum Electrodynamics -- chapter 9 Functional Calculus -- chapter 10 Free Fields in the Schrodinger Representation -- chapter 11 Interacting Fields in the SchrOdinger Representation -- chapter 12 Path Integral Representation of Quantum Mechanics -- chapter 13 Path Integrals in Free Field Theory -- chapter 14 Interacting Fields and Path Integrals -- chapter 15 Yang-Mills and Faddeev-Popov -- chapter 16 Hiding the Infinities -- chapter 17 Renormalization of QED at 1-Loop -- chapter 18 The Effective Action -- part II STRINGS -- chapter 19 Basic Ideas and Classical Theory -- chapter 20 First Quantization -- chapter 21 The Mathematics of Surfaces -- chapter 22 Polyakov's Integral: The Partition Function for Genus 0 -- chapter 23 Higher-Genus Integrals -- chapter 24 Scattering Amplitudes -- chapter 25 Noncritical Dimensions -- chapter 26 Introduction to Superstrings.
Keywords: Quantum field theory; String models